The 2022 Russia-Ukraine Conflict: Multimodal Framing Analysis of Chinese Mainstream Media Coverage on Douyin - Wang, Yao; Sharul Nazmi Sannusi (Penerbit Universiti Kebangsaan Malaysia, 2024)
The mainstream media plays an essential role in the modern war in selecting the facts and making them salient. Prior research has concentrated on framing diverse wars from multiple perspectives, either verbal-only, visual-only or both. However, as the Russian and Ukrainian war constantly escalates, the multimodal framing of Chinese media video coverage on social media platforms (Douyin) has yet to be explored systematically and comprehensively. Therefore, the main objective of this study is to analyse how Chinese mainstream media apply multimodal frames (verbal, visual and aural) to construct their tendencies regarding the 2022 Russian and Ukrainian conflict on social media (Douyin). Based on multimodal framing analysis, the findings revealed that Chinese mainstream media on Douyin preferred the verbal frames of the military conflict and human interest, the visual frames of officials, combat and war machines, and the “stirring/tense” aural frame. Meanwhile, they had a neutral position and a pro-Russia slant. These multimodal framing strategies presented distinct relationships with slants. Specifically, only one morality verbal frame statistically correlates with particular slants. Surprisingly, no visual frames have a correlation with different news slants and all the aural frames are observed to have a statistical correlation with distinct slants. This study offers a multimodal perspective to framing analysis in international war reporting in the Chinese context. In practice, it might also offer valuable insights for mainstream media to enhance their narrative strategies when covering war videos on social media platforms.